Epidemiological and clinical characteristics of dengue and zika infections during the El Niño Costero phenomenon in 2017 in Chincha, Peru - Reátegui, Alexander (2021)
The aim of this study was to determine the clinical and epidemiological characteristics of the confirmed cases of Zika and dengue, presented during the El Niño Costero phenomenon, period January-June 2017 and that were treated at the Health Centre of the Pueblo Nuevo district, province of Chincha, in Ica, Peru. An observational, descriptive and retrospective study was designed that systematized demographic information, clinical signs and the time elapsed between the beginning of these and the investigation, notification and confirmation of the cases. In total, 130 confirmed positive cases for Zika and 44 for dengue were recovered. The greatest number of cases were reported between epidemiological weeks 12 and 15 and in women (76.9% of Zika and 63.6% of dengue). The greatest number of Zika and dengue cases occurred in the age group of 20-29 years (30.0 and 27%, respectively). The most frequent clinical signs in both cases were exanthema, headache, myalgia, ocular/retrocular pain and arthralgia/polyarthralgia. The relationship between the temporal behaviour of the cases and the interventions carried out show that the nebulization application had a greater effect, reducing the number of confirmed cases after the application. It is concluded that early recognition and notification of the presence of dengue and zika, as well as the use of nebulization for vector control have a direct impact on the number of new cases of these diseases in a non-endemic area.